Normal Values of Metatarsal Parabola Arch in Male and Female Feet - Gabriel Domínguez-Maldonado; Pedro V. Munuera-Martinez; José Manuel Castillo-López; Javier Ramos-Ortega; Manuel Albornoz-Cabello (The Scientific World Journal)
There is not any method to measure metatarsal protrusion in the whole metatarsal. The aim of this research is to know the normal metatarsal parabola in male and female feet. The system of measurement devised by Hardy and Clapham to evaluate the protrusion between metatarsals I and II was adapted to study the whole metatarsal parabola and applied to the five metatarsals of 169 normal feet, 72 female feet and 97 male feet. Authors measured all metatarsal protrusion relative to metatarsal II. The results obtained show a female metatarsal protrusion relative to metatarsal II of +1.27% for metatarsal I, -3.36% for metatarsal III, -8.34% for metatarsal IV, and -15.54% for metatarsal V. Data obtained for male metatarsal parabola were +0.5% for metatarsal I, -3.77 for metatarsal III, -9.57 for metatarsal IV, and -17.05 for metatarsal V. Differences between both metatarsal parabola were significant.